Analisis dan Perancangan Sistem Karcis Elektronik Pada Gerbang Masuk Busway Dengan Menggunakan RFID - Suryadiputra Liawatimena (Bina Nusantara University, 2010)
The aim of this study is to use Radio Frequency technology to facilitate human activities, especially used in Busway entrances. In this research methodologies used include field survey to the BP Transjakarta; literature study by reading manuals, text books, journals, and articles on the Internet, and conduct laboratory experiments on the Bina Nusantara University Hardware Research Laboratory in designing and making the minimum system . Based on the results of an experiment and taking data on the minimum system, it can be concluded in general the performance of the system is running well, but the response time was not optimal. Some improvements to the system needed to improve system performance, such as raising response time, improved data security, and online systems.